TECHNOLOGY-ENABLED IMPLEMENTATION OF INCLUSIVE EDUCATION POLICIES: A SYSTEMATIC REVIEW OF UDL, MTSS, AND LEARNING ANALYTICS - Widya Angelia; Ardin Sianipar; Natalina Damayanthi (Universitas Pelita Harapan, 2026)
This article synthesises evidence on the implementation of inclusive education policies by examining the interplay of technology, pedagogical frameworks, and systemic support in shaping adoption, consistency, adherence, and feasibility across various school contexts. Design/methodology/approach: A Systematic Literature Review (SLR) was conducted in accordance with the PRISMA 2020 guidelines. Seventeen Scopus-indexed articles (2016–2024) were analysed, focusing on study characteristics, theoretical foundations, and implementation indicators. Quality was assessed using JBI checklists. Findings reveal that the combination of assistive technologies, learning management systems, and analytics dashboards enhances adoption and consistency when paired with teacher professional development and Leadership support. The UDL and MTSS frameworks strengthen coherence in curriculum adaptation and monitoring. Nevertheless, affordability, teacher readiness, and infrastructure gaps particularly in LMICs remain significant challenges. Temporal differences emerged: pre-COVID studies emphasised classroom level interventions, while post COVID research highlighted systemic digital infrastructure and accountability. Research limitations include reliance on English only sources, methodological heterogeneity, and potential publication bias. Implications: Policymakers must align inclusion mandates with funding and infrastructure, while school leaders should integrate teacher training and data driven monitoring to support inclusive practices. Researchers are encouraged to adopt mixed method and longitudinal designs across contexts. This study presents a comparative synthesis of pre and post COVID literature, highlighting systemic strategies and justice-oriented perspectives as crucial for sustaining inclusive education.